Entrepreneurship during the Covid-19 Pandemic: A global study of entrepreneurs' challenges, resilience, and well-being - Stephan, Ute; Zbierowski, Przemyslaw; Pérez-Luño, Ana; Klausen, Anna; Alba Cabañas, Marisleidy; Barki, Edgard; Benzari, Alexandre; Bernhard-Oettel, Claudia; Boekhorst, Janet; Dash, Arobindu; Efendic, Adnan; Eib, Constanze; et al. (2021)
Summary: Small and medium-sized enterprises (SMEs including the self-employed) account for 90% of businesses globally and provide 70% of employment worldwide. These businesses, typically entrepreneur led, are threatened by the Covid-19 pandemic, meaning that millions of jobs are at risk. This report presents insights from a global study conducted during the pandemic in 2020. We surveyed over 5,000 entrepreneurs in 23 countries that represent 3/4 of the world’s economic output. Most entrepreneurs faced significant challenges threatening the survival of their businesses. We also see resilience in how entrepreneurs navigated the crisis through being agile, adaptive, and exploring new opportunities, utilizing government support, giving back to society, and even harbouring growth ambitions beyond the pandemic. Entrepreneurs’ mental well-being dropped by 12% in the pandemic presenting another threat to their businesses. We chart stressors and well-being resources including social support and self-care strategies that entrepreneurs engaged to stay productive. We close the report (1) by reflecting on five trends for the post-Covid economy and formulate actionable policy recommendations of how entrepreneurs and SMEs can be supported in light of these trends (digitalisation; ‘local’ focus, inclusive business models, developing personal and business resilience), and (2) offer five practical steps for entrepreneurs to protect their well-being.